Dynamics and spatialization of the coffee production of Minas Gerais State betwee 1990 and 2008 using geotechnologies - Souza, Vanessa Cristina Oliveira de; Vieira, Tatiana Grossi Chquiloff; Volpato, Margarete Marin Lordelo; Alves, Helena Maria Ramos (Coffee Science - ISSN 1984-3909, 2012)
The aim of this study was to identify coffee cropped areas and production spatial patterns in the state of Minas Gerais between 1990 and 2009. IBGE and Statistic Coffee Yearbook data were used. The data was treated by the TerraView Geographic Information System, which overlaid the coffee information with the state’s district cartographic division. During the years studied, the cultivated area increased by 17.13%. The South/Southwest, Zona da Mata and Northern regions presented the highest growth. The regions Central Mineira and Vale do Mucuri had their coffee areas reduced. The production of the Zona da Mata and South/Southwest regions of the state increased. There was also a reduction of 20.46% in the number of districts that produce up to 50,000 60 kg bags of coffee per year. A comparison of the IBGE and Statistic Coffee Yearbook data evidenced a large discrepancy between the official statistics, which showed a greater alignment only from the year 2002 onwards.